On the use of hourly pricing in techno-economic analyses for solar photovoltaic systems. (15th September 2015) - Sommerfeldt, Nelson; Madani, Hatef
Highlights: The typical price year (TPY) method is described. The impact of pricing simplification models on revenues and NPV are tested. The TPY is shown to be a good long-term price curve for techno-economic studies. A static mean annual price can replace hourly in the Swedish market with minimal error. Abstract: The use of hourly prices in distributed photovoltaic (PV) techno-economic analysis is rare, but may become necessary as time-of-day retail pricing becomes more common. A methodology is presented for selecting an hourly price curve suitable for long-term analysis, called the typical price year (TPY), which is based on the methodology for TMY weather data. Using a techno-economic analysis with annual revenues and net present value as indicators, a TPY curve for the Swedish market is validated and then compared to 18 price simplification methods to determine the error introduced by the use of non-hourly prices. Results show that the TPY method produces a curve which accurately represents long term pricing trends, but using a static annual mean introduces minor revenue errors of 1.3%. This suggests the TPY may not be necessary in the Swedish market, but further analysis of the method is suggested for other markets.